Impact of supply chain collaboration and knowledge sharing on organizational outcomes in pharmaceutical industry of Bangladesh - Haque, Mahbubul; Islam, Rafikul (Emerald Publishing Limited, 2018)
Purpose – This study investigates the proposed relationships concerning the supply chain collaboration practices & knowledge sharing with organizational performance in the pharmaceutical industry of a developing country.